The Ijtihad of Female Judges in Aceh’s Sharia Courts: Disparity in Sentencing for Child Sexual Abuse - Fauziati, Fauziati; Abbas, Syahrizal; Devy, Soraya; Husnul, Muhammad; Suarni, Suarni (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
This study examines the ijtihad (independent reasoning) undertaken by female judges in the Sharia Court when imposing sentences on perpetrators of child sexual abuse. It highlights the variations in the judges’ verdicts, which include punishments such as caning and imprisonment, as well as sentences that differ—either higher or lower—from the demands of the Public Prosecutor. This study utilized an empirical juridical method, combining statutory analysis with the maqashid al-sharia (objectives of Islamic law) approach. Data were gathered through interviews with female judges and a review of judicial decisions, journal articles, books, research reports, and legal regulations. The findings reveal that female judges’ ijtihad in sentencing child sexual abusers has been driven by trial evidence and the best interests of the child. The judges typically approve of imprisonment as a means of limiting contact between the perpetrator and the victim, in order to safeguard the child from further trauma. Within the framework of maqashid al-sharia, the verdicts of these female judges have been in line with the principles of protecting the interests and security of the child, as the main objective of Islamic law. This study suggests that courts review the caning rules in the Qanun Jinayat and consistently prioritize the child’s best interests while imposing penalties.